How Climate Change Disrupts Mango Phenology and Affects Fruit Production - Hamzah, Andi Siady; Ngakan, Putu Oka; Kaimuddin, Kaimuddin; Nasri, Nasri; Putra, Putu Supadma; Mas'ud, Wardiman (Jurnal Penelitian Kehutanan Wallacea, 2025)
Climatic elements are limiting factors for plants; therefore, climate change can impact the phenology of plants. This study aims to determine the impact of climate change on the reproductive phenology of four local mango cultivars on Sulawesi Island, Indonesia. Data were collected during 2013 and 2014 by observing and recording the production of vegetative shoots, generative shoots, and fruits from the trees of each mango cultivar weekly. To assess the impact of seasonal change on fruit quality, the weight and sugar level of the ripe fruits in each cultivar were measured. Climate data were obtained from the National Centers for Environmental Prediction and the Indonesian Agency for Meteorology, Climatology, and Geophysics Region IV, Makassar. Results show that from 1979 until 2014, the climate in the study site changed from type D to type C according to the Schmidt-Ferguson Climate Classification method, indicating that the wet season became longer. Following climate change, the reproductive phenology of the four mango cultivars also changed from once to twice annually, whereby the flush of vegetative and reproductive shoots that appeared during the first period in March did not successfully develop into mature fruit but developed following the second period in July. The change of season also impacted the quality of the mangoes, as fruit produced during the longer dry season had higher sugar levels than those produced during the shorter dry season.